1991
DOI: 10.1111/j.1532-5415.1991.tb02497.x
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Disruptive Vocalizations among Geriatric Residents in Nursing Homes

Abstract: This paper reports the results of a controlled study comparing geriatric residents in nursing homes who displayed disruptive vocalizations with residents in a comparison group. Two 350-bed nursing homes were surveyed, and it was found that 11% of the residents engaged in disruptive vocalizations, at least once per week, of sufficient severity to require consideration in the resident's care plan. Results show that disruptive vocalizers were more functionally impaired and were more likely to receive a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
3
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(142 citation statements)
references
References 20 publications
5
130
3
4
Order By: Relevance
“…For example, in an observational study of 175 elderly persons with dementia, CohenMansfield and Libin (2005) found verbally agitated behaviors to be associated with female gender, cognitive decline, poor ADL performance, impaired social functioning, and depressed affect. These findings corroborated those of previous studies (Cariaga et al, 1991;CohenMansfield et al, 1992). Physically non-aggressive behaviors were positively related to cognitive impairment and negatively related to number of concurrent medical diagnoses.…”
Section: Introductionsupporting
confidence: 83%
“…For example, in an observational study of 175 elderly persons with dementia, CohenMansfield and Libin (2005) found verbally agitated behaviors to be associated with female gender, cognitive decline, poor ADL performance, impaired social functioning, and depressed affect. These findings corroborated those of previous studies (Cariaga et al, 1991;CohenMansfield et al, 1992). Physically non-aggressive behaviors were positively related to cognitive impairment and negatively related to number of concurrent medical diagnoses.…”
Section: Introductionsupporting
confidence: 83%
“…An alternative approach is the evaluation of behavioral manifestations of pain. [16] [100] and investigators have demonstrated that observational methods of evaluating pain behaviors are psychometrically sound when used with the general population (e.g., acute pain, communicative patients with chronic lower back pain, and osteoarthritic knee pain) and that the behaviors are sensitive to treatment effects. [73] [121] The utility and validity of these approaches with cognitively impaired older adults, however, has yet to be determined.…”
Section: Observational Methodsmentioning
confidence: 99%
“…Unsurprisingly, frequency estimations depend on how VDB is defined. Thus, breaking down VDB, the frequency of screaming was found in 51% of VDB, abusive language in 37%, moaning in 33%, repetitive verbalizations in 25%, and other vocalizations in 17% (Cariaga et al, 1991). Similarly, frequencies varied depending on the presumed etiology of VDB: purposeless and persistent noisemaking in 9% to 10.4% of cases, noise-making as a response to the environment in 6.5% to 9.4%, noise-making that appears directed towards eliciting a response from the environment in 3.9% to 7%, "chatterbox" noise-making in 1.6% to 2.8%, noise-making in the context of deafness in 1.2% to 1.4%, and other noisemaking in 2.5% to 4.4% (Ryan et al, 1988).…”
Section: Prevalence Of Vdbmentioning
confidence: 99%
“…VDB may therefore reflect an underlying need to communicate discomfort due to pain, thirst, hunger, and inappropriate room temperature which may be undetected or ignored by staff (McMinn and Draper, 2005) or be the response to inappropriate mental or physical stimuli (Draper et al, 2000). Indeed, patients in nursing homes with VDB were prescribed analgesic drugs less often than those without VDB (Cariaga et al, 1991). Furthermore, caregivers' attitudes towards nursing home patients may well be one of the causes of disruptive behaviors since communication may reflect attitudes held towards a patient (Burgener et al, 1992).…”
Section: Factors Causing Vdbmentioning
confidence: 99%
See 1 more Smart Citation